The Role of Digital Marketing as a Company Strategy to Gain a Competitive Advantage in Dealing with Consumer Behavior in the Era of the Industrial Revolution 4.0 - Pashiera, Resa Salsa; Sardjono, Wahyu (Universitas Batanghari Jambi, 2024)
In the rapidly evolving landscape of Industry 4.0, companies are forced to adapt their marketing strategies to meet the challenges posed by shifting consumer behavior. This article explores the critical role of digital marketing as a strategic tool for companies looking to achieve and maintain a competitive advantage in this transformative era. Using a qualitative research approach, this study explores aspects of consumer behavior and the effectiveness of digital marketing strategies. By gathering information from various sources, including journals related to the theme of digital marketing. By focusing on qualitative aspects, this research aims to provide a comprehensive understanding of the ways in which digital marketing contributes to building brand awareness, driving customer engagement and shaping consumer loyalty in the context of Industry 4.0. The research also investigates the adaptability of companies in adjusting their digital marketing strategies to align with changing consumer behavior. The research conclusion states that the complexity of challenges and opportunities in digital marketing practices requires a deep understanding and innovative approaches. Digital marketing is poised to take a leading role, with numerous marketers exploring innovative methods for online sales, cost-effective lead generation, enhanced click-through and conversion rates, and the exploration of emerging trends in the digital marketing landscape. This article delves into comprehending the concepts of digital marketing and how companies can attain a competitive advantage. While the data may not cover all of the available literature, this research remains the foundation for further understanding and development of more effective marketing strategies in the ever-evolving digital age.